The laws of the Federation of Nigeria and Lagos : in force on the 1st day of June, 1958, v. 5 - Kingdon, Donald (London : Printed by Eyre and Spottiswoode, 1959)
This edition consists of twelve volumes: the first six volumes comprise the Ordinances, 224 chapters arranged in alphabetical order; a chronological table of Ordinances and Laws is also included in volume 1; volumes 7, 8, 9 and 10 cover the subsidiary legislation; volume 11 includes some Imperial Statutes and Royal Orders in Council relating to Nigeria, together with subsidiary legislation thereunder; volume 12 contains an index of the whole edition.
ne 18/10/2019
Loans
Keywords: Law; Nigeria